Third-Generation Cephalosporin Resistance in Intrinsic Colistin-Resistant Enterobacterales Isolated from Retail Meat - Justice Opare Odoi; Sayo Takayanagi; Montira Yossapol; Michiyo Sugiyama; Tetsuo Asai (MDPI AG, 2021)
Consumption of retail meat contaminated with antimicrobial-resistant (AMR) bacteria is a common route for transmitting clinically relevant resistant bacteria to humans. Here, we investigated the genotypic and phenotypic resistance profiles of intrinsic colistin-resistant (ICR) Enterobacterales isolated from retail meats. ICR Enterobacterales were isolated from 103 samples of chicken, 103 samples of pork, and 104 samples of beef purchased from retail shops in Japan, using colistin-containing media, and their antimicrobial susceptibility was examined. Serratia spp. (440 isolates) showed resistance to cefotaxime (19 isolates, 4.3%), tetracycline (15 isolates, 3.4%), and other antimicrobials (<1%). Hafnia spp. (136) showed resistance to cefotaxime (12 isolates, 8.6%), ceftazidime (four isolates, 2.9%), and tetracycline (two isolates, 1.4%). Proteus spp. (39) showed resistance to chloramphenicol (four isolates, 10.3%), sulfamethoxazole-trimethoprim (four isolates, 10.3%), cefotaxime (two isolates, 5.1%), kanamycin (two isolates, 5.1%), and gentamicin (one isolate, 2.6%). Cedecea spp. (22) were resistant to tetracycline (two isolates, 9.1%) whereas Morganella spp. (11) were resistant to tetracycline (four isolates, 36.4%) and chloramphenicol (one isolate, 9.2%). The resistance genes blafonA, blaACC, and blaDHA were detected in cefotaxime-resistant Serratia spp., Hafnia spp., and Morganella spp. isolates, respectively. This emergence of antimicrobial resistance in ICR Enterobacterales may pose a public health risk.